Mesmerized : how Ben Franklin solved a mystery that baffled all of France - Rockliff, Mara (Candlewick Press, 2015)
Discover how Benjamin Franklin's scientific method challenged a certain Dr. Mesmer's mysterious powers in a whimsical look at a true moment in history.